Structural, Electronic, and Optical Properties of Zinc Oxide Nanosheets in the Presence of Cadmium Impurities - Razieh Beiranvand (فیزیک کاربردی ایران)
Zinc oxide (ZnO) nanosheets, recognized as one of the semiconductor materials with unique characteristics, have garnered significant attention in various scientific and industrial fields in recent years. Due to their relatively high band gap (approximately 3.3 electron volts) and ability to absorb light in the ultraviolet region, this material is widely used in light-emitting diodes, sensors, and solar cells. This study examines a comprehensive range of structural, electronic, and optical properties of this material within the framework of density functional theory (DFT). The results indicate that the presence of cadmium impurities in zinc oxide nanosheets significantly affects the structural, electronic, and optical properties of these materials. Incorporating cadmium into the zinc oxide structure can lead to notable changes in the crystal lattice and enhance structural stability. These changes may result in a reduction of crystal defects and an increase in the surface-to-volume ratio, which in turn positively impacts the optical and electronic properties of the nanosheets. Furthermore, cadmium impurities can lead to a reduction in the band gap and an increase in the overall magnetic moment of the material. These modifications may create new electronic states within the nanosheet structure, contributing to the enhancement of optical properties, including light absorption and emission, and improving optical characteristics for applications in photovoltaic devices.